Population structure of invasive Neisseria meningitidis in the United States, 2011–15. Issue 5 (November 2018) - Potts, Caelin C.; Joseph, Sandeep J.; Chang, How-Yi; Chen, Alexander; Vuong, Jeni; Hu, Fang; Jenkins, Laurel T.; Schmink, Susanna; Blain, Amy; MacNeil, Jessica R.; Harrison, Lee H.; Wang, Xin
Highlights: N. meningitidis population structure was stable 10 years after vaccine introduction. Significant capsular switching was not detected, 2011–15. The two genetic lineages in serogroup W, CC11 and CC22, were regionally associated. Genomic analysis allowed classical & high resolution meningococcus characterization. Summary: Objectives: Meningococcal conjugate vaccines (MenACWY) were licensed in the United States in 2005. We assessed the population structure of invasive Neisseria meningitidis (Nm) ten years after recommended use of MenACWY among adolescents. Methods: Meningococcal isolates obtained through Active Bacterial Core surveillance (ABCs) from 2000–05, 2006–10, and 2011–15 underwent whole genome or Sanger sequencing. Genome phylogenies were completed using maximum likelihood methods; and distribution of multilocus sequence typing (MLST) sequence type (ST) and clonal complex (CC), and PorA and FetA types were assessed. Results: Prevalent serogroups (B, C, Y and W), CCs, and PorA and FetA types were detected in all three time periods, but dynamic changes were observed. The proportion of serogroup W CC11 isolates increased in 2011–15 and were most related to South American strains. Changes in CC distribution were also observed in serogroup C and serogroup Y. Phylogenetic analysis showed that U.S. serogroup W CC11s are closely related to a subset of U.S. serogroup C isolates; combined global analysis demonstrated that some CCs, including CC11, exhibit regional clustering. Conclusions: Overall, the Nm population structure has remained stable after MenACWY introduction. Dynamic changes in genotypes, unlikely related to vaccination, also occurred, highlighting the need for continued whole genome-based surveillance.